Building resilience in German primary care practices: a qualitative study - Litke, Nicola; Weis, Aline; Koetsenruijter, Jan; Fehrer, Valeska; Koeppen, Martina; Kuemmel, Stephanie; Szecsenyi, Joachim; Wensing, Michel (BMC primary care, 2022)
In recent years, healthcare has faced many different crises around the world such as HIV-, Ebola- or H1N1-outbrakes, opioid addiction, natural disasters and terrorism attacks). In particular, the current pandemic of Covid-19 has challenged the resilience of health systems. In many healthcare systems, primary care practices play a crucial role in the management of crises as they are often the first point of contact and main health care provider for patients. Therefore, this study explored which situations are perceived as crises by primary care practice teams and potential strategies for crisis management.
Gesehen am 24.10.2022